Agricultural Biotechnology's Complementary Intellectual Assets - Graff, Gregory D.; Rausser, Gordon C.; Small, Arthur A. (The Review of Economics and Statistics, 2003)
We formulate and test a hypothesis for the dramatic restructuring that the plant breeding and seed industry has recently undergone: the reorganization can be explained in part by the desire to exploit complementarities between intellectual assets needed to create genetically modified organisms. This hypothesis is tested using data on agricultural biotechnology patents, notices for field tests of genetically modified organisms, and firm characteristics. The presence of complementarities is identified with a positive covariance in the unexplained variation of asset holdings. Results indicate that coordination of complementary assets has increased under the consolidation of the industry.